Prokinetic and Laxative Effects of Chrozophora tinctoria Whole Plant Extract - Ayaz Ali Sher; Arshad Iqbal; Naveed Muhammad; Syed Lal Badshah; Abdul-Hamid Emwas; Mariusz Jaremko (Molecules, 2022)
Chrozophora tinctoria (Euphorbiaceae) has been used as an emetic, anthelminthic, and cathartic agent in traditional medicine. We used gas chromatography-mass spectrometry (GC-MS) to characterize the composition of ethyl acetate (EAC) and dichloromethane (DCMC) fractions from the whole Chrozophora tinctoria plant. EAC and DCMC fractions were evaluated for acetylcholinesterase (AChE) inhibitory activity and acute toxicity. Their effects on intestinal propulsive movement and spasmogenic activity of the gastrointestinal tract (GIT) muscle were also assessed. The compounds detected in both fractions were mostly fatty acids, with about seven compounds in EAC and 10 in DCMC. These included pharmacologically active compounds such as imipramine, used to treat depression, or hexadecanoic acid methyl ester, an antioxidant. Both EAC and DCMC fractions inhibited acetylcholinesterase (AChE) activity with IC50 values of 10 µg and 130 µg, respectively. Both the fractions were found to be toxic in a dose-dependent manner, inducing emesis at 0.5 g or higher and lethargy and mortality from 3–5 g upwards. Similarly, both of the fractions showed laxative activity in metronidazole- and loperamide-induced constipation models. EAC relaxed the intestinal muscle at a lower dose (1 mg/mL) than DCMC. Similarly, the EAC extract showed a significant relaxation effect (EC50 = 0.67 ± 0.15 mg/mL) on KCL-induced contraction in rabbit jejunum as compared to DCMC (EC50 = 5.04 ± 0.05 mg/kg). The present study strongly supports the folklore that this valuable plant is a cathartic agent. Further work is required to isolate and validate the bioactive compounds that act as diarrheal agents in Chrozophora tinctoria.